THE IMPLEMENTATION OF SCIENTIFIC APPROACH IN TEACHING ENGLISH IN SENIOR HIGH SCHOOL PEKANBARU - Apriauny, Lestari; Nababan, Mangihut; ', Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is aimed at investigating how the English teachers implement the Scientific Approach (SA) in teaching English in Senior High School in Pekanbaru. The research design is a categorized as a qualitative research under interpretive research paradigm. There were 3 English teachers selected as the participants of this research. The instruments used in this research were an interview question (semi-structured) and classroom observation. The data were analyzed qualitatively by using Gay’s theory (2000). The result of the study showed that the English teachers in Senior High School Pekanbaru encountered problems dealing with understanding the concept of SA and the implementation of the Curriculum 2013 in classroom activities. Data from semi-structured interviews indicate that participants of this research did not seem to have a clear understanding on the five stages of Scientific Approach in teaching English. However, data from the classroom observation show that some teachers have implemented some stages of the approach quite well, especially in observing, questioning, and experimenting. Finally, it is suggested for the English teachers to get more knowledge and skills in implementing the Scientific Approach as determined by the 2013 Curriculum.Keywords: Curriculum, Implementation, Scientific Approach, Teaching English